Assessment of epidemiological factors and clinical profiles of cerebral infarction cases in tertiary health center in southern Maharashtra and hence evaluating computed tomography as its diagnostic modality: a prospective study - Jadhav, Nitin; Rode, Vikram (International Journal of Research in Medical Sciences, 2017)
Background: Cerebrovascular accidents are one of the leading causes of death in developed countries. The advent of CT in early 1970s greatly facilitated the diagnosis and management of stroke. The present study aims at assessing epidemiological factors and clinical presentation of cerebral infarction cases and hence to evaluate computed tomography as a diagnostic tool for cerebral infarction. Methods: A prospective study was carried out among cases of Cerebral infarction. Every patient was interviewed personally, and detailed history was taken followed by clinical, systemic and neurological examination. Results were analysed comparing clinical diagnosis, sites of lesions, nature of lesions and CT scan findings. Results: Cases showed male predominance with 69% cases and 31% were females. 19% cases presented with headache, 17% with convulsions and 9% with vomiting. Upon eliciting past history of cases, we found that 48% were known cases of hypertension, 23% were having past history of cerebrovascular episodes, 20% cases were smokers and tobacco chewers whereas 15% were known cases of diabetes mellitus. Conclusions: Currently India is facing double burden of communicable and non-communicable diseases, and now a day’s cases of non-communicable diseases have started increasing, following iceberg phenomenon. So, diagnosing these conditions in its initial stage and halting the disease progress will be the priority. The present study recommends a comprehensive model for non-communicable disease prevention and control based on current healthcare needs and disease scenario.